1996
DOI: 10.1111/j.1467-9787.1996.tb01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative Feedbacks in the Economy and Industrial Location*

Abstract: Incorporating regional asymmetry and negative feedbacks (congestion) in a model of economic geography and international trade shows that complete specialization of production at one location is unlikely. We identify an agglomerating force: the home market effect, and two spreading forces, competition for demand from immobile sectors of production and congestion. We demonstrate that negative feedbacks can explain the economic viability of small industrial regions observed in the real world. Simulations clarify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
5

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 12 publications
1
39
0
5
Order By: Relevance
“…Ce mouvement est renforcé par l'introduction d'un coût de transport du bien attaché au sol (Calmette et Le Pottier, 1995) et, surtout, d'un différentiel de coût de transport entre bien attaché au sol et bien industriel (Kilkenny, 1998). La prise en compte de coûts urbains liés à la concurrence pour l'occupation du sol (Péguy et al, 2000) ou à des effets de congestion (Brackman et al, 1996) se traduit par un mouvement de dispersion tant des activités que des populations, dispersion engendrée par l'agglomération elle-même. L'introduction d'un avantage comparatif dans la région peu dense (Ricci, 1999) montre que celle-ci peut attirer des firmes mobilisant cet avantage s'il compense les pertes dues à l'éloignement du marché de la région dense.…”
Section: Les Forces D'agglomération Et De Dispersionunclassified
“…Ce mouvement est renforcé par l'introduction d'un coût de transport du bien attaché au sol (Calmette et Le Pottier, 1995) et, surtout, d'un différentiel de coût de transport entre bien attaché au sol et bien industriel (Kilkenny, 1998). La prise en compte de coûts urbains liés à la concurrence pour l'occupation du sol (Péguy et al, 2000) ou à des effets de congestion (Brackman et al, 1996) se traduit par un mouvement de dispersion tant des activités que des populations, dispersion engendrée par l'agglomération elle-même. L'introduction d'un avantage comparatif dans la région peu dense (Ricci, 1999) montre que celle-ci peut attirer des firmes mobilisant cet avantage s'il compense les pertes dues à l'éloignement du marché de la région dense.…”
Section: Les Forces D'agglomération Et De Dispersionunclassified
“…Other models deal with more than two regions (e.g. Brakman et al, 1996;Fujita et al, 1999, chapt. 6).…”
Section: Introductionmentioning
confidence: 99%
“…There are models that incorporate congestion (e.g. Brakman et al, 1996;Suedekum, 2006) and commuting costs (e.g. Tabuchi, 1998;Borck et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This poses empirical problems because there are many cities of different sizes throughout the world. Brakman et al (1996) overcome this discrepancy through a model incorporating congestion costs, which ensures that the powers of agglomeration and spreading are more easily balanced, allowing for many cities of different sizes. Brakman et al (1999) use this approach to explain the empirically observed city-size distribution across space (rank-size rule/Zipf's Law).…”
Section: Introductionmentioning
confidence: 99%